A presença dos contos de fadas nos processos formativos das professoras de educação infantil - Auricchio, Rosana (2012)
This research had as its object of study, the presence of fairy tales in the formative processes of the teachers of an Early Childhood Center in the Municipality of São Paulo. The objective was to understand how fairy tales were manifested in the practices and discourse of these teachers. The reason for this research relates to my work as a teacher who works in an Early Childhood Center, concerned with how and with what is offered to young children in terms of stories. For the research I opted for a qualitative approach to data collection procedure used to analyze literature and documents supplemented by reports from my own experience and from colleagues who work as teachers in Early Childhood Center Captain Mario Caldana in training meetings, about the presence of fairy tales in their life stories and professional performance. I realized through research that the term means different fairy tales stories, among which emerged as part of the formative process of the teachers stood out beyond the fairy tales, the "stories", the biblical stories, folk tales, etc. Furthermore, it was revealed that many of the stories worked in schools, are adaptations made by the cultural industry, chosen more for ease of access than as a result of a pedagogical discussion.